2021
DOI: 10.3390/sym13060974
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer and Biomaterial Conjugated Iron Oxide Nanomaterials as Prostate Cancer Theranostic Agents: A Comprehensive Review

Abstract: Prostate cancer (PCa) is the most common malignancy in men and the leading cause of death for men all over the world. Early diagnosis is the key to start treatment at an early stage of PCa and to reduce the death toll. Generally, PCa expresses characteristic morphologic features and serum biomarkers; however, early diagnosis is challenging due to its heterogeneity and long-term indolent phase in the early stage. Following positive diagnosis, PCa patients receive conventional treatments including surgery, radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 125 publications
0
6
0
Order By: Relevance
“…Excellent photosensitivity makes PFNPs an innovative tool for the detection and treatment of ovarian cancer cells [ 43 ]. In in vitro studies, overexpression of prostate stem cell antigen (PSCA) was identified in 90% of samples where the ability of mAbs to identify PSCA was significantly increased by the use of conjugate–dextran antibodies with superparamagnetic iron oxide [ 44 ]. As such, the labeled cell produces intense blue color upon binding with anti-PSCA-dextran-superparamagnetic iron oxide [ 45 ].…”
Section: Current Developmental Status Of Abc In Oncologymentioning
confidence: 99%
“…Excellent photosensitivity makes PFNPs an innovative tool for the detection and treatment of ovarian cancer cells [ 43 ]. In in vitro studies, overexpression of prostate stem cell antigen (PSCA) was identified in 90% of samples where the ability of mAbs to identify PSCA was significantly increased by the use of conjugate–dextran antibodies with superparamagnetic iron oxide [ 44 ]. As such, the labeled cell produces intense blue color upon binding with anti-PSCA-dextran-superparamagnetic iron oxide [ 45 ].…”
Section: Current Developmental Status Of Abc In Oncologymentioning
confidence: 99%
“…In recent years, the use of polysaccharide nanoparticles for the diagnosis of various diseases has become relevant [ 104 , 105 ]. Nanoparticles of biopolymers can be loaded with various substances, providing highly synergistic effects and diagnostic/therapeutic efficiency [ 106 , 107 ].…”
Section: Main Applications Of Biodegradable Polymeric Nanoparticlesmentioning
confidence: 99%
“…Based on Figure 3, the molecular weight (Mw) and the DA of CS are the two most important structural characteristics that influence the polymer's overall behaviour as a biomaterial [34]. Commercially available CS with a wide range of DA and Mw (DA 35% and Mw between 10 and 800 kDa), with low Mw defined as less than 50 kDa, medium Mw defined as between 50 and 150 kDa, and high Mw defined as greater than 150 kDa [35]. Other than that, water, concentrated acid, alkali, alcohol, and acetone, as well as typical organic solvents, are all insoluble in CS.…”
Section: Chitosan As a Natural Polycationic Linear Polysaccharidementioning
confidence: 99%